Habitat Characteristics and Population of Booted Macaque (Macaca ochreata) in Tanjung Peropa Wildlife Reserve , Southeast Sulawesi - Zsa Zsa , Zsa Zsa Fairuztania; Abdul , Abdul Haris Mustari (Jurnal Wasian, 2017)
Macaca ochreata is one of Sulawesi endemic primates, which are distributed only in Southeast Sulawesi. This study aimed to identify habitat characteristics and estimated Macaca ochreata population was conducted in February until March of 2017 at Kalobo Block Forest, Tanjung Peropa Wildlife Reserve (TPWR). Habitat characteristics were identified using vegetation analysis and population was estimated by concentration count method. The highest Important Value Index of trees were Pangium edule, Artocarpus elastica, and Meliostoma nitida which were Macaca ochreata’s food plants. There were 33 species of 17 families of Macaca’s food plants on the study site. Macaca ochreata were found in trees with stratum B and stratum C. A total of 4 groups of Macaca ochreata encountered consisting 56 individuals. Population density of Macaca ochreata was 22,4 individu/km2.